Analisis Pendapatan Petani Karet Kecamatan Bantan Kabupaten Bengkalis - Dedi Arianto; Hendro Ekwarso; Dahlan Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in Bantan Districts since Mei 2014. This study aims to to find out pattern of income distribution in the rubber farmers in the Bantan District, Data used are primary and secondary data. Primary data obtained through interviews, observation and dissemination kuistioner to a population of 507 families of rubber farmers in the Teluk Pambang village and 496 families in the village of Bantan Tengah, the number of each sample were 21 rubber farmers. While the secondary data obtained from the appropriate agencies. Methods of data analysis of this study using quantitative descriptive method then uses the Gini Index Ratio method and the Lorenz Curve. From the analysis we found that the Gini constant value of 0.1941 in the Teluk Pambang village whereas in Bantan Tengah village of 0.2524, then H0 is rejected. This shows that income distribution of rubber farmers in the village of Teluk Pambang more evenly than Bantan Tengah village.Keywords: Distribution of Income, Poverty and Gini Index Ratio